Reconstruction of a Large Anterior Ear Defect after Mohs Micrographic Surgery with a Cartilage Graft and Postauricular Revolving Door Flap - Stephanie Nemir; Lindsey Hunter-Ellul; Vlad Codrea; Richard Wagner (Hindawi Limited, 2015)
A novel postauricular revolving door island flap and cartilage graft combination was employed to correct a large defect on the anterior ear of an 84-year-old man who underwent Mohs micrographic surgery for an antihelical squamous cell carcinoma. The defect measured 4.6 × 2.4 cm and spanned the antihelix, scapha, a small portion of the helix, and a large segment of underlying cartilage, with loss of structural integrity and anterior folding of the ear. The repair involved harvesting 1.5 cm2 of exposed cartilage from the scaphoid fossa and then sculpting and suturing it to the remnant of the antihelical cartilage in order to recreate the antihelical crura. The skin of the posterior auricle was then incised just below the helical rim and folded anteriorly to cover the cartilage graft. The flap remained attached by a central subcutaneous pedicle, and an island designed using the full-thickness defect as a stencil template was pulled through the cartilage window anteriorly to resurface the anterior ear. This case demonstrates the use of the revolving door flap for coverage of large central ear defects with loss of cartilaginous support and illustrates how cartilage grafts may be used in combination with the flap to improve ear contour after resection.